2017
DOI: 10.1128/aem.02946-16
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enrichment of Dehalococcoides-Like Bacteria by Partial Hydrophobic Separation

Abstract: Organohalide-respiring bacteria can be difficult to enrich and isolate, which can limit research on these important organisms. The goal of this research was to develop a method to rapidly (minutes to days) enrich these organisms from a mixed community. The method presented is based on the hypothesis that organohalide-respiring bacteria would be more hydrophobic than other bacteria as they dehalogenate hydrophobic compounds. The method developed tests this hypothesis by separating a portion of putative organoha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…On the contrary, norank_p_Aminicenantes , which appeared with a high abundance, played an important role in the bio-PRB under TCE stress. Although Acidovorax has been described as capable of degrading BTEX [ 24 , 67 , 68 ], its poor tolerance to TCE stress meant that it hardly contributed to BTEX biodegradation in our experiment.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…On the contrary, norank_p_Aminicenantes , which appeared with a high abundance, played an important role in the bio-PRB under TCE stress. Although Acidovorax has been described as capable of degrading BTEX [ 24 , 67 , 68 ], its poor tolerance to TCE stress meant that it hardly contributed to BTEX biodegradation in our experiment.…”
Section: Resultsmentioning
confidence: 70%
“…Besides the small percentage of unclassified bacteria, Proteobacteria were the most abundant (relative abundance of 35.9–79.7%) phylum, followed by Bacteroidetes (1.51–20.9%) and Ignavibacteriae (1.15–9.82%) ( Figure 9 A). Since Ignavibacteriae , Bacteroidetes , Aminicenantes , and Proteobacteria are frequently found in BTEX-impacted environments [ 24 , 66 , 67 , 68 ], the present work focused on these four dominant phyla. The relative abundance of Proteobacteria increased with the influent concentration of benzene and toluene, which indicated that Proteobacteria had a strong tolerance to a high concentration of benzene and toluene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation